التعليم الالكتروني للأجيال القادمة: E-Learning for Future Generations - Issa Mohamed Al-Yahya’i, Nawal; Mohamed Adnan, Mohamad Azrien; Awae, Fareed (Journal Al-Muqaddimah, 2023)
This scientific paper attempts to give a brief picture of e-learning for future generations. It aims to clarify two objectives. The first one is to know what e-learning is, what its types are, and what its characteristics are. The second one is to record its advantages and disadvantages. Consequently, the goals, characteristics, advantages, and constraints of e-learning are codified. The researcher has adopted an analytical-descriptive approach. Finally, the study concluded a set of findings, of which the most important is that e-learning is a modern method of education in which modern techniques and communication mechanisms are used to support the educational process. Moreover, e-learning provides an interactive environment with a multifaceted, mobile, individual, and holistic variety, which plays a role in solving the obstacles or reasons for reluctance toward education. In fact, e-learning has characteristics and advantages such as speed, flexibility, low cost, and easy access to a teacher without effort or hardship. While its disadvantages are that it is easy to penetrate examinations, get answers to questions, and use others in solving tests. Moreover, society sees e-learning system graduates as less efficient and skilled than traditional education system graduates.